Impact of Irrigation on Yield Attributes of Seven Wheat Genotypes (Bangladesh Journal of Botany, 2021)
Seven wheat genotypes i.e., PR-110, PR-112, PR-115, PR-118, PR-119, PR-120 and Pirsabak-13 were evaluated at: I0: Control, I1: irrigation at seedling stage, I2: irrigation at seedling and booting stages, I3: irrigation at seedling, tillering and booting stages and I4: irrigation at seedling, tillering, booting and grain formation stages. Among the genotypes, PR-115, PR-118 and PR-120 were found to be superior for grain yield and its related attributes under full and deficit water conditions. Irrigation at seedling + tillering + booting stages + grain formation stages (I4) produced statistically higher yield and related traits. It was also observed that in case of water shortage, irrigation at seedling and booting stages reduced the drastic losses in grain yield of wheat. The study suggested that identified promising wheat genotypes can be utilized in future breeding programs to develop drought tolerant varieties.Bangladesh J. Bot. 50(2): 235-243, 2021 (June)